2017
DOI: 10.1063/1.5009089
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets of epitaxial cubic boron nitride deposited on polycrystalline diamond via plasma-enhanced chemical vapor deposition

Abstract: Cubic boron nitride (c-BN) has been deposited on nitrogen-doped polycrystalline diamond films via plasma-enhanced chemical vapor deposition employing fluorine chemistry. Transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) were utilized to characterize the c-BN/diamond interface. TEM observations indicated local epitaxy of c-BN on diamond, while h-BN was also observed at the interface. XPS measurements indicated that c-BN growth continued after nucleation. The band offsets between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Diamond has been reported as a perfect nucleation surface for epitaxial growth of c-BN due to the small lattice mismatch of these two materials [3,4,21,22]. Epitaxy of c-BN/diamond is attracting significant attention for both basic crystal engineering and optoelectronic applications.…”
Section: T E Dmentioning
confidence: 99%
“…Diamond has been reported as a perfect nucleation surface for epitaxial growth of c-BN due to the small lattice mismatch of these two materials [3,4,21,22]. Epitaxy of c-BN/diamond is attracting significant attention for both basic crystal engineering and optoelectronic applications.…”
Section: T E Dmentioning
confidence: 99%
“…The latter is accordance to a recent report in which VBM of c-BN was inferred to be 0.8 eV above that of diamond for C-N interfacial bonding. 36 However, the previous theoretical calculations demonstrated that the c-BN VBM positioned at least 1.9 eV below the diamond VBM in the (100) surface for C-B bondings and 0.13 eV for C-N bondings. 35 In addition, the c-BN VBM was found to be 0.71 eV lower than that of diamond as to the (110) hetero-interface with one mixed C-B and C-N layer.…”
Section: Band Offsetsmentioning
confidence: 90%
“…Experiments have already shown that along certain crystallographic orientations, [100] and [111], it is possible to grow a C|BN heterostructure. [28][29][30][31][32] Unlike the C|BN heterostructures of two bulk phases, [25,31,33] in present exploratory study a cBN "monolayer" is sandwiched, so the band offset between identical diamond phases is well defined (e.g., exactly zero in the absence of cBN)-convenient model to explore the offset dependence on crystallographic directions or BN thickness. We examine below how the cBN shifts the electronic band structure of diamond, and eventually facilitates the modulation doping, [34] assuming the free charge carriers and donors/acceptors would be in different diamond regions, separated by the cBN interface.…”
Section: Introductionmentioning
confidence: 99%